A Python toolkit to monitor sandy shoreline change using high-resolution PlanetScope cubesats. (November 2022) - Doherty, Yarran; Harley, Mitchell D.; Vos, Kilian; Splinter, Kristen D.
Abstract: This study evaluates an emerging capability to monitor high spatial (pixel size = 3.7 m) and temporal (daily to sub-daily imagery) resolution coastal change using PlanetScope cubesats. A new toolkit ( CoastSat.PlanetScope ) is presented that enables users to map shorelines from PlanetScope imagery, using a workflow of image co-registration, segmentation, thresholding, shoreline detection and elevation correction. The toolkit is subsequently tested at Narrabeen-Collaroy Beach (SE Australia), evaluating combinations of shoreline detection indices, thresholding approaches and elevation correction. An optimal shoreline accuracy of 3.5 m (RMSE) is found for this coastline using the difference between the near-infrared and blue bands and a weighted peaks thresholding approach. A generic elevation correction model that considers tidal variability and wave setup at the shoreline is then proposed. With a growing archive of high-resolution imagery, PlanetScope presents enormous potential for enhanced coastline mapping of the coast and complements existing approaches using Landsat/Sentinel-2 imagery. Highlights: A new toolkit introduced to map shoreline change from PlanetScope cubesat images. Validation at microtidal sandy beach indicates horizontal accuracy of 3.5m. Capable of mapping shoreline change from individual storm events.